Molecular dynamics simulation of CO2-switchable surfactant regulated reversible emulsification/demulsification processes of a dodecane–saline system. Issue 41 (15th October 2020) - Zhang, Lihu; Lu, Xiancai; Liu, Xiandong; Li, Qin; Cheng, Yongxian; Hou, Qingfeng
Abstract : CO2 -Switchable surfactants have great potential in a wide range of industrial applications related to their ability to stabilize and destabilize emulsions upon command. Abstract : CO2 -Switchable surfactants are of great potential in a wide range of industrial applications related to their ability to stabilize and destabilize emulsions upon command. Molecular dynamics simulations have been performed to reveal the fundamental mechanism of the reversible emulsification/demulsification processes of a dodecane–saline system by a CO2 -switchable surfactant that switches between active ( i.e., N ′-dodecyl- N, N -dimethylacetamidinium (DMAAH + )) and inactive ( i.e., N ′-dodecyl- N, N -dimethylacetamidine (DMAA)) forms. The density profiles indicate that DMAAH + could increase the oil–water interfacial thickness to a greater extent compared to DMAA. DMAAH + could sharply reduce the interfacial tension of the dodecane–saline system, while DMAA only exhibits a limited decrease, which is in accordance with the experimental observation that DMAAH + /DMAA can reversibly emulsify/demulsify alkane–water systems. Our simulations showed that both the number and lifetime of hydrogen bonds (HBs) between DMAA and water are almost equal to those between DMAAH + and water. In DMAA, the N atom connecting with the alkyl tail acted as a HB acceptor, while the N atom attached by a proton in DMAAH + acted as a HB donor. Furthermore, the HBs between DMAAH + and HCO3 − at the interfaces are relatively limited. Hence, it is deduced that the HBs are insufficient to achieve the CO2 -switchability of DMAA/DMAAH + . The Lennard Jones and coulombic potentials between DMAA/DMAAH + and other species show that the coulombic potentials between DMAAH + and water or anions ( i.e., Cl − and HCO3 − ) sharply decrease with the increase of DMAAH + and are much lower than those in models with DMAA. The enhanced coulombic interactions between DMAAH + and anions lead to a remarkable reduction in interfacial tension and the emulsification of the alkane–saline system. Therefore, coulombic interactions are of crucial importance to the reversible emulsification/demulsification processes regulated by CO2 -switchable surfactants, namely DMAAH + /DMAA.